Implementation of intersectoral community approaches targeting childhood obesity: a systematic review. Issue 6 (30th March 2015) - van der Kleij, R.; Coster, N.; Verbiest, M.; van Assema, P.; Paulussen, T.; Reis, R.; Crone, M.
Summary The implementation of intersectoral community approaches targeting childhood obesity (IACO) is considered challenging. To help overcome these challenges, an overview of the evidence to date is needed. We searched four databases to identify papers that reported on the determinants of successful implementation of IACOs, resulting in the inclusion of 25 studies. We appraised study quality with the Crowe Critical Appraisal Tool and the Quality Framework; reported implementation outcome indicators were reviewed via narrative synthesis. Quality of included studies varied. The most frequently reported indicators of implementation success were fidelity and coverage. Determinants related to the social‐political context and the organization were most often cited as influencing implementation, in particular, 'collaboration between community partners', 'the availability of (human) resources' and 'time available for implementation'. The association between determinants and implementation variability was never explicated. We conclude that although some insights into the effective implementation of IACOs are present, more research is needed. Emphasis should be placed on elucidating the relationship between determinants and implementation success. Research should further focus on developing a 'golden standard' for evaluating and reporting on implementation research. These actions will improve the comparison of study outcomes and may constitute the cumulative development of knowledge about the conditions for designing evidence‐based implementation strategies.